Nitrogen and Phosphorus Interplay in Lupin Root Nodules and Cluster Roots - Pueyo, José J.; Quiñones, Miguel A.; Coba de la Peña, Teodoro; Fedorova, Elena E.; Lucas, M. Mercedes (Frontiers in Plant Science, 2021)
Nitrogen (N) and phosphorus (P) are two major plant nutrients and their deficiencies often limit plant growth and crop yield. The uptakes of N or P affect each other, and consequently, understanding N–P interactions is fundamental. Their signaling mechanisms have been studied mostly separately, and integrating N–P interactive regulation is becoming the aim of some recent works. Lupins are singular plants, as, under N and P deficiencies, they are capable to develop new organs, the N2-fixing symbiotic nodules, and some species can also transform their root architecture to form cluster roots, hundreds of short rootlets that alter their metabolism to induce a high affinity P transport system and enhance synthesis and secretion of organic acids, flavonoids, acid phosphatases and proton efflux. These modifications lead to mobilization in the soil of, otherwise unavailable, P. White lupin (Lupinus albus), represents a model plant to study cluster roots and for understanding plant acclimation to nutrient deficiency. It tolerates simultaneous P and N deficiencies, and also enhances uptake of additional nutrients. Here, we present the structural and functional modifications that occur in conditions of P and N deficiencies, and lead to the organogenesis and altered metabolism of nodules and cluster roots. Some known N and P signaling mechanisms include different factors, including phytohormones and miRNAs. The combination of the individual N and P mechanisms uncovers interactive regulation pathways that concur in nodules and cluster roots. L. albus interlinks N and P recycling processes both, in the plant itself and in nature.